1979
DOI: 10.1159/000232189
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and Inhibitory Effects of Cyclic AMP on Lymphocytes from Atopic Children

Abstract: The effect of cholera toxin and dibutyryl cAMP on mitogen-activated lymphocytes from atopic and non-atopic individuals was studied. Cholera toxin enhanced stimulation by phytohemagglutinin of cells from small children but not from adults. Dibutyryl cAMP at low concentration (< 10––5M) significantly enhanced the lymphocyte response to mitogens in some, but not all individuals. High concentrations, on the other hand, were consistently inhibitory. In atopic children, the lymphocyte response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It has been reported that the proliferation of lym phocytes from atopies is more sensitive to inactiva tion by cylic AMP-elevating agents than are cells from nonatopic donors [8,9], Therefore, the possibili ty was raised that the decreased viability of atopic cells observed in the present study might be associated with altered reactivities to cAMP-promoting, physio logically occurring substances. In order to test this possibility, MNC were cultured in the presence or ab sence of high concentrations of theophylline (2 x 10'3 M) or dibutyryl AMP (10~3 M).…”
Section: Effect Of Theophylline and Dibuturyl Cyclic Amp On Cell Viabmentioning
confidence: 58%
See 1 more Smart Citation
“…It has been reported that the proliferation of lym phocytes from atopies is more sensitive to inactiva tion by cylic AMP-elevating agents than are cells from nonatopic donors [8,9], Therefore, the possibili ty was raised that the decreased viability of atopic cells observed in the present study might be associated with altered reactivities to cAMP-promoting, physio logically occurring substances. In order to test this possibility, MNC were cultured in the presence or ab sence of high concentrations of theophylline (2 x 10'3 M) or dibutyryl AMP (10~3 M).…”
Section: Effect Of Theophylline and Dibuturyl Cyclic Amp On Cell Viabmentioning
confidence: 58%
“…The numbers and mitogen responsiveness of T cells in atopy are decreased [1] and there also ap pears to be a shift in the balance between different subset of T cells at least in cases of severe atopy [2][3][4][5][6][7], Furthermore, the atopic lymphocytes are character ized by an altered response to cyclic AMP-inducing agent manifested as an apparently decreased response to the inducing agents [10] and as a greater sensitivity to the proliferation-inhibiting effect of such agents [8,9]. Some results suggest that atopic lymphocytes have a reduced sensitivity to the proliferation-enhancing effects of normal serum factors [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is a re markable similarity, however, between dose-response curves obtained in mitogen-induced lymphocyte pro liferation assays [Strannegard and Strannegard, 1979] and the presently described IgE system. Therefore it is possible that the stimulatory effect of cAMP-elevating agents on IgE synthesis reflects a general capacity of these agents to stimulate lymphocyte-mediated re sponses.…”
Section: Discussionmentioning
confidence: 69%
“…Both inhibitory and enhancing effects have been ascribed to this substance [reviewed by Strom et al, 1977], Mitogen-induced lymphocyte proliferation is inhibited by high concentrations (> 10'5 M) of cAMP whereas low concentrations have been found to stim ulate proliferation in humans [Strannegard and Strannegard, 1979]. There is no clear explanation for this dual effect of cAMP, but it has been suggested that certain suppressor cells are unusually sensitive to inactivation by cAMP and, therefore, preferential in activation of such cells might lead to enhancement of immune responses [Katz and Fauci, 1978;Strannegard and Strannegard, 1978].…”
Section: Introductionmentioning
confidence: 99%
“…Kümmeret al [16] have recently shown that transition of T4+ to T8* cells and Tu to Ty cells is positively influenced by adeno sine, and prostaglandin E2 appears to induce expres sion of the FclgG receptor on human T cells [19], Since these substances increase intracellular cyclic AMP levels and the response to several cyclic AMPactive agonists is decreased in AD [28], it is possible that the observed imbalance between T lymphocyte subsets is secondary to a basic defect in cyclic AMP induction or degradation. Another possible explana tion for a suppressor cell deficiency in atopy would be that certain suppressor cells are sensitive to cyclic AMP-mediated inactivation [20,33] and T lympho cytes from atopies appear to be more sensitive than cells from nonatopics to such inactivation [35]. Dis tinguishing between these possibilities will have to await further characterization of suppressor cells that regulate IgE synthesis.…”
Section: Discussionmentioning
confidence: 99%